STUDI KUALITATIF PELAKSANAAN PEMANTAUAN PERTUMBUHAN ANAK BALITA DI POSYANDU DI KABUPATEN BANDUNG - Aditianti Aditianti; Erna Luciasari; Yurista Permanasari; Elisa Diana Julianti; Meda Permana (Persagi, 2018)
ABSTRACT Integrated health service (Posyandu) is one form of strategic health effort, which provides public health services. One of the posyandu function is as promotion media and growth monitoring of children under five. The purpose of this research was to know the implementation of child growth monitoring at posyandu level in Bandung district. This was an operational studies with qualitative design.Data were collected by depth interview, focus group discussion, and observation. The population of this research were all of the institution that responsible of nutrition surveillance. There were Regencies District Health Office, Primary Health Center (Puskesmas), and Posyandu, in Bandung District, West Java. This research is operational research with qualitatif design. Colected data used with indepth interview, focus group discusion and observasi. Indepth interview used to offices, health workers from two community health centers, and village officials. Group discussions were conducted on cadres and mothers of underfives children. This research show posyandu activities have been going well but have not implemented monitoring function of child growth. Plot weight were not doing well in KMS, interpretation of child growth were still unsuitable, and counseling had not done well. Repositioning of posyandu is needed as a means of growth monitoring children under five years and efforts to increase knowledge about routine growth monitoring for health workers and cadres. Keyword: growth monitoring, integrated health service, under five years old Abstrak Pos pelayanan terpadu (Posyandu) merupakan salah satu bentuk upaya kesehatan yang strategis, yang menyediakan layanan kesehatan masyarakat. Salah satu fungsi posyandu adalah sebagai media promosi dan pemantauan pertumbuhan anak umur bawah lima tahun (balita). Penelitian ini bertujuan untuk mengetahui pelaksanaan pemantauan pertumbuhan balita di tingkat posyandu di Kabupaten Bandung, Jawa Barat. Penelitian ini merupakan penelitian operasional dengan desain kualitatif. Pengumpulan data melalui wawancara mendalam, diskusi kelompok terarah. Wawancara mendalam dilakukan kepada petugas di dinas kesehatan kabupaten, tenaga kesehatan dari dua pukesmas terpilih, dan aparat desa. Diskusi kelompok dilakukan pada kader dan ibu balita, dan. Hasil penelitian menunjukkan bahwa kegiatan posyandu sudah berjalan baik namun belum melaksanakan fungsi pemantauan pertumbuhan balita. Masih banyak yang tidak melakukan plot hasil penimbangan pada KMS (kartu menuju sehat), interpretasi terhadap perubahan berat badan belum dilakukan dengan benar dan konseling yang belum berjalan baik. Perlu dilakukan reposisi posyandu sebagai sarana pemantauan pertumbuhan balita dan upaya untuk meningkatkan pengetahuan tentang pemantauan pertumbuhan secara rutin bagi tenaga kesehatan dan kader. [Penel Gizi Makan 2018, 41(1):41-54] Kata kunci: pemantauan pertumbuhan, pos pelayanan terpadu, bawah lima tahun (balita)